ANALYSIS OF THE LEVEL OF PUBLIC ACCEPTANCE TOWARDS THE USE OF QRIS AS A FINANCIAL TECHNOLOGY IN LABUHANBATU REGENCY - Pristiyono; Suci Cahaya Anggraini; Nur Febri, Muhammad (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
The main objective of this study is to prove the influence of performance expectancy, effort expectancy and social influence variables on the decision to use QRIS as a financial technology, in addition, the study aims to determine that QRIS is one of the effective and efficient financial technologies in Labuhanbatu Regency. The number of samples studied was 100 respondents, the sample collection technique used was purposive sampling. From the results of the QRIS acceptance index from the three regencies, different aggregates were obtained and were above 30%. The results of the study showed that based on the respondent profile of gender, age and education, QRIS users as a financial technology payment tool were dominated by women and millennials or generation Z. The research variable that chose the greatest influence on the decision to use QRIS as a financial technology was the social influence variable compared to performance expectancy and effort expectancy. In general, the results of this study succeeded in proving that the use of QRIS as a financial technology payment tool can be well accepted by the community